DAMPAK IMPLEMENTASI PERDA NO 5 TAHUN 2022 TENTANG RELOKASI PEDAGANG KAKI LIMA DI KOTA MEDAN (Program Studi PPKn, Fakultas Keguruan dan Ilmu Pendidikan Universitas Buana Perjuangan Karawang, 2025)
This study aims to analyze the Impact of the Implementation of Regional Regulation No. 2022 Concerning the Relocation of Street Vendors in the city of Medan. It is important to analyze the impact of the implementation of Regional Regulation No. 5 of 2022, both from the positive and negative sides, so that the policies taken can provide optimal solutions for all parties, especially for street vendors and the people of Medan City in general. In this study, the approach used is qualitative descriptive. The data required in this study is qualitative, so the analysis method applied is qualitative descriptive analysis. The results of this study indicate that the Socialization and guidance carried out by Satpol PP have taken place, although the intensity tends to decrease from year to year. . Although the government has made various efforts, this policy still needs improvement to present a comprehensive solution in managing street vendors and improving the quality of the Medan City environment. Keywords: Impact of implemention,Street Vendors,Regional Regulation No.5 of 2022,Relocation.